Experimental study of a tunable perfect flexural wave absorber with a piezoelectric shunted resonator - Li, Xiaopeng; Yu, Ziqi; Lee, Taehwa (Frontiers in Physics, 2022)
Metamaterials and metasurfaces have been widely developed recently for extraordinary acoustic and elastic wave control at a deep subwavelength scale. Perfect wave absorption as an extreme case to totally absorb the impinged waves has gained great attention, whereas most existing designs based on local resonance lack tunabilities, making perfect absorption be observed at a single frequency. To overcome this drawback, in this work, we design and fabricate a programmable inductance-resistance (LR) shunted mechanical resonator via a bonded piezoelectric patch for total flexural wave absorption at low-frequency. The approach proposed provides an alternative solution to achieve perfect wave absorption in the low-frequency range and enables practical application in complex engineering structures.